2009
DOI: 10.1260/135101009788913239
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acoustical Environments in Eating Establishments

Abstract: The acoustical environments, and the acoustical conditions to which customers and workers are exposed, were evaluated in ten existing eating establishments. The perceived quality of the EE acoustical environments for customers and employees, and how respondent-related factors and the EE acoustical characteristics affect it, were investigated. These objectives were achieved by way of physical and acoustical measurements, and customer and employee questionnaires and their statistical analysis. Summary statistics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…Restaurants are designed to look aesthetically pleasing and modernized, which often is portrayed with a lack of materials used to absorb sound. The lack of these materials tends to increase the overall noise level in the restaurant which has caused diners, critics, audiologists and researchers to take notice 1 , 3 , 5 – 12 . In 2018, a repeated restaurant survey revealed noise was the primary complaint of restaurant patrons 12 .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Restaurants are designed to look aesthetically pleasing and modernized, which often is portrayed with a lack of materials used to absorb sound. The lack of these materials tends to increase the overall noise level in the restaurant which has caused diners, critics, audiologists and researchers to take notice 1 , 3 , 5 – 12 . In 2018, a repeated restaurant survey revealed noise was the primary complaint of restaurant patrons 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Typical restaurant noise can fluctuate throughout the course of an evening ranging from 65 dB(A) up to as high as 85 dB(A) 1 , 3 , 4 , 7 , 13 . This causes increased difficulty to be heard and understood by anyone 4 , 5 , 10 , 13 . The main source of noise in a restaurant is caused by the patrons, as a consequence several researches suggested that dining establishments should no longer be thought to have “maximum capacity” but rather “acoustical capacity” 5 , 6 , 10 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations